Tax Reforms and Intertemporal Shifting of Wage Income: Evidence from Danish Monthly Payroll Records - Skov Ebbesen, S; Kreiner, C. T.; Leth-Petersen, S. (American Economic Association (AEA), 2016)
This paper uses monthly payroll records for all Danish employees to identify widespread intertemporal shifting of labor income in response to a tax reform that significantly reduced the marginal tax rates for one-fourth of all employees. When ignoring shifting, the estimate of the overall elasticity of taxable income equals 0.1, and the elasticity is increasing with earnings. When removing the shifting component, the elasticity is close to zero at all earnings levels. The evidence also indicates that tax salience, liquidity constraints and firm willingness to cooperate in shifting are important factors in explaining shifting behavior